Exercise, Dialysis, and Environment: A Narrative Review in an Ecological Perspective - Giovanni Piva; Alda Storari; Yuri Battaglia; Fabio Manfredini; Nicola Lamberti (Karger Publishers, 2024)
Background: Patient empowerment and environmental sustainability may contribute to creating efficient and resilient healthcare models. Chronic kidney diseases call for a sustainable approach aimed at improving physical function and mental health of patients and possibly contributing to the slowing down of the evolution toward the end stage of renal disease (ESRD) with a reduction of the environmental and economic impact. Summary: Multidisciplinary interventions should be implemented particularly, at the final stages when patients are exposed to sedentariness, reduced health-related quality of life (HR-QoL), high cardiovascular morbidity and mortality, and the healthcare services to high costs, and participation in environmental pollution. Ecological strategies based on specific nutritional approaches, exercise, and environment should be designed and tested. In particular, the introduction to physical exercise represents a useful replacement therapy to counteract the hazards derived from the sedentary behavior of ESRD patients, with low physical function associated with poor clinical outcomes. A more active and healthy lifestyle, particularly in the natural environment, could impact HR-QoL, mental and physical well-being but also on socialization, with lower anxiety and fatigue stress levels. Otherwise, combining sustainable exercise models into the patient's daily routine can be enhanced by the biophilic design called to reproduce a natural environment in the dialysis center. Finally, the involvement of the personnel and the health professionals in properly managing the exercise interventions and the related factors (location, modality, dose, intensity, and duration) might improve the patients' participation. In particular, ecological programs should be broadly inclusive and aimed to target the lowest performing populations through minimal feasible doses of exercise. Key Messages: Moving toward an ecological framework of lifestyle change in the very advanced stages of kidney disease, the potential synergies between environment, diet, and exercise may improve the physical and mental health of the patients and reduce the impact of dialysis.